Media and Accounting Education. - Mead, George C.; Shenkir, William G. (The Accounting Review, 1970)
In the social sciences today Marshall McLuhan's probings have caused much discussion, and certainly accounting educators should not overlook his views on the way media affect the way students think and learn. If his views on contemporary society and media are accurate, the trend today is toward participation. Students conditioned by a television environment must participate in the learning process, or they will become disinterested. Accounting educators should recognize this fact and seek media which arouse participation, not indoctrinate students. The media used in accounting education should be viewed as extensions of the profession and should be chosen not only for their ability to reveal content but for the image they project of the accounting profession-a viable profession with many controversial issues to be solved. A byproduct of the accounting education process may then be the disappearance of the myth that " '⃛ accounting is cut and dried and all its problems have been solved by electronic computers.' " 22 In addition, participatory courses attuned to student's learning needs may aid in attracting talented people into the accounting profession.